Expression of DNA repair genes in association with ionizing radiation: Radiation and DNA repair - Machi Jr, Amaury; Moreira Perez, Matheus; Luciano da Veiga, Glaucia; Cristiano Pereira, Edimar; Adami, Fernando; Alves, Beatriz; Fonseca, Fernando (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: DNA repair systems are functionally essential for the maintenance of life and among these, we can highlight the MutS system, subdivided into MutSα (hMSH2 and hMSH6) and MutSβ (hMSH2 and hMSH3). The objective of this study was to analyze the expression of hMSH2 and hMSH6 repair genes in radiology technicians exposed to low radiation doses.Methods: Thirty workers occupationally exposed to ionizing radiation and twenty-five non-exposed were included in this study. Gene expression was analyzed by qPCR. Peripheral blood samples were collected from both groups for total RNA isolation.Results: It was observed a five-fold increase (p=0.006) in the hMSH2 repair gene expression in those exposed to radiation and a weak but significant correlation (p=0.041) with the hMSH6 genes when we associated the number of hours of exposure with gene expression.Conclusions: The longer the exposure time, the greater the activation of this component of the repair system. Application to Practice: Blood count parameters could did not alter with radiation exposure. X-rays used by radiology technicians in imaging tests can damage the DNA to the point of activating the MutS repair system and that there is a greater tendency of expression of this system in professionals that had undergone longer exposure.